How online focusing events influence policy agenda setting in China: a qualitative comparative analysis - Li, Miao; Ma, Zhihao (Frontiers in Political Science, 2025)
Policy agenda-setting is a crucial indicator of a political system’s nature and openness, reflecting the political attitudes and value orientations of its decision-makers. In China’s authoritarian context, where centralised control and strategic governance dominate, the rise of online political engagement has made Internet-based focusing events key drivers in shaping policy agendas. This study examines how these events influence policy prioritisation within the Chinese political system. Utilising Qualitative Comparative Analysis (QCA), this research develops a framework that incorporates ‘actor-driven’ and ‘opportunity-coupling’ factors to explore the impact of these events on policy formulation. The findings reveal that the Chinese government strategically manages its responsiveness to public discourse, aligning policy shifts with broader state objectives. By analysing the dynamics of policy-setting in China’s digital age, this study enhances the understanding of how authoritarian resilience is maintained through the interaction between state control and online public engagement.